Multiple object constructions in P'orhepecha : argument realization and valence-affecting morphology - Capistrán-Garza, Alejandra (Brill's studies in the indigenous languages of the Americas ;, 2015)
In this monograph, Capistrán analyzes constraints on double and triple object sentences following a PO/SO pattern. Alternating constructions and construction splits are also explained. PO selection according to a thematic ranking accounts for the (un)grammaticality of tritransitive constructions.